SUMBER DAYA MANUSIA, OPERASIONAL, PEMASARAN, DAN KEBIJAKAN PEMERINTAH TERHADAP KINERJA UMKM DI KOTA SURABAYA - Rindik Rita Purwaningsih; Nadia Asandimitra Haryono (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, The research aims to determine the effect of financial literacy, financial behavior, human resources, operations, marketing, and government policies on the performance of MSMEs in the city of Surabaya. Measurement of variables using a Likert scale with forty-three statements and for financial literacy variables also uses the Guttman scale with five questions. The sample used in this study were 108 MSME respondents, registered as assisted by the Surabaya Office of Cooperatives and Micro Business in 2018. Data is collected using questionnaires. The data analysis technique uses multiple regression analysis with the SPSS application. The results of the analysis showed that the financial behavior of business owners and marketing had an effect on the performance of MSMEs in Surabaya, meaning that the better financial behavior of business owners and the better marketing can improve business performance.